Family income with less chronic energy (LCE) in pregnant women - Nurul Utami R; Mustamin Mustamin; Agustian Ipa (Jurusan Gizi Poltekkes Kemenkes Makassar, 2018)
Less of chronic energy is a condition caused by an imbalance of nutrient intake between energy and protein, so that the nutriens needed are not fulfilled. As for pregnant woman said to be less chronic energy if the measurement of the upper arm circumference is less than 23.5 cm. The results of Riskesdas in 2016 showed the prevalence of pregnant women lacking chronic energy at the National level as much as 16.2% and monitoring of nutritional status in 2017 in South Sulawesi showed the prevalence of KEK pregnant women in the island’s Pangkajene district 25.08%. This study aims to determine the relationship of family income with less chronic energy for pregnant women in the work area of the Bungoro Health Center. This research is observational analytic. The research location was carried out in the work area of the Bungoro Health Center in may 2018. The results of the study showed that there were 24 people (80%) who were not chronically energetic in pregnant women, while 6 people were not in chronic energy (20%). Data of pregnant woman lacking chronic energy is done by interview method using questionnaires and LLA measurements. The results of the study obtained from the chi-square test showed that there was no family income relationship with less chronic energy in pregnant women in the work area of the Bungoro Community Health Center in Bungoro sub-district, Pangkep district where the value p=0,620 (>0,05). To reduce the less of chronic energy in pregnant women in Bungoro sub-district, Pangkep District conducted counseling for pregnant women to pay more attention to the health and consumption of nutritious foods during pregnancy, and cross-sector cooperation between the government and rhe health department to conduct an examination of pregnant women so that they could take precautionary measures against pregnant women who less chronic energy.